Malnutrition in the Critically Ill Child: The Importance of Enteral Nutrition - Prieto, Marta Botrán (Molecular Diversity Preservation International (MDPI), 2011)
Malnutrition affects 50% of hospitalized children and 25–70% of the critically ill children. It increases the incidence of complications and mortality. Malnutrition is associated with an altered metabolism of certain substrates, increased metabolism and catabolism depending on the severity of the lesion, and reduced nutrient delivery. The objective should be to administer individualized nutrition to the critically ill child and to be able to adjust the nutrition continuously according to the metabolic changes and evolving nutritional status. It would appear reasonable to start enteral nutrition within the first 24 to 48 hours after admission, when oral feeding is not possible. Parenteral nutrition should only be used when enteral nutrition is contraindicated or is not tolerated. Energy delivery must be individually adjusted to energy expenditure (40–65 kcal/100 calories metabolized/day) with a protein delivery of 2.5–3 g/kg/day. Frequent monitoring of nutritional and metabolic parameters should be performed.